SUPPLY CHAINS FOR INNOVATION ACTIVITY IN REGIONAL INDUSTRIAL SYSTEMS IN POLAND – SOME EVIDENCE FROM EMPIRICAL RESEARCH - Świadek, Arkadiusz (Ekonomia i Prawo. Economics and Law, 2015)
Space and relations with suppliers and customers are significant determinants of innovativeness in industry not only in Poland, but also in much more developed countries. In industrial systems at their early phases of development, high tech solutions are usually owned by a relatively small number of enterprises, usually foreign ones. It affects the slow and limited diffusion of knowledge in regions without connection to an international chains of knowledge flow. In a such cases enclaves of innovation usually have a one-sided rather than system character based on the synergy of events. This research study has proved that described conditions are important for innovation activity in every regional industrial system, therefore these factors should be considered in innovative strategies.